AL USLUB FII AN NAQD AL BALAGHY - Fajrina, Fitria (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aimed at discovering various uslub used in the Arabic language. The researcher used library research and analyzed it by utilizing the theories of balaghah and analyzing how native speakers use their Arabic. Every language has its way of the technique of structuring words. Moreover, this way of technique means the method or the style used to share one's ideas and feelings so that they reach to their supposed target and could be understood by all the readers or the listeners. So does it what occur in the Arabic language that has various ways of teaching which will not only focus on the shift of reading marks but also on diction, subjects positioning, verbs, or objects those who play a role in making the way if teaching happen. To see a level of Arabic language proficiency, the way one uses uslub with its relevancy to the situation and condition can be seen as one parameter. Furthermore, the discussion on uslub cannot be separated from ilm balaghoh. Ilm balaghoh consists of 3 fields of discussion such as albayan, al maani, and al badi which have interlinked relation with uslub. This is because even each field might have its focus to be discussed, they will still collide in the discussion of uslub.